Perception, Attitude and Intention towards COVID-19 Vaccination - Aarti Chahal; Rosy Dhall; Jyotika Kundu; Nidhi Kataria (Medical Sciences Forum, 2023)
To overcome the situation due to the COVID-19 pandemic, vaccination became essential. So, it is important to understand the overall perception, attitude, and intention of the general population towards vaccination. This study aimed to investigate the combined effect of usefulness and trust on the attitude towards COVID-19 vaccination and to understand the perceptions of vaccinated and unvaccinated people towards vaccination. The self-administered questionnaire was used to collect the data. In the descriptive research design, Structural Equation Modeling was used to test the combined effect of usefulness and trust on attitudes towards COVID-19 vaccination and one-way ANOVA was used to test the difference in perceptions of vaccinated and unvaccinated people. Simple random sampling was used in this study. The questionnaire-based data were collected from 400 respondents in Haryana from 24 April 2021 to 13 May 2021. The results showed that more than 70% of the respondents were not vaccinated, around 16% received their one dose of a vaccine, and less than 15% received two doses of a vaccine. Usefulness and trust had an impact on the attitude towards vaccination. There was significant difference between those who did not receive any doses of a vaccine, i.e., either Covishield (viral vector vaccine) or Covaxin (inactivated viral vaccine), and those who received two doses of a vaccine. The results reveal that attitude is strengthened by a positive relationship between trust and usefulness. Even though there were a large number of people who were not vaccinated at the time of the survey, these people had a positive perception of the vaccine. Hence, they were most likely to get vaccinated in the future. It was also found that the vaccine history of the respondents played an important role in future vaccination intention. Awareness programs are important as people need to be well informed about the benefits of vaccination.